2020
DOI: 10.1109/jtehm.2020.2985058
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable System for Attenuating Essential Tremor Based on Peripheral Nerve Stimulation

Abstract: Objective: Currently available treatments for kinetic tremor can cause intolerable side effects or be highly invasive and expensive. Even though several studies have shown the positive effects of external feedback (i.e., electrical stimulation) for suppressing tremor, such approaches have not been fully integrated into wearable real-time feedback systems. Method: We have developed a wireless wearable stimulation system that analyzes upper limb tremor using a three-axis accelerometer and that modulates/attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…The tremor reduction results observed at the end of IntraStim sessions (short-term effect) are in line with the results reported by others using SurfStim [10]- [12], [28]. All patients who received SATS during IntraStim session (6 out of 6) reduced their tremor during the assessment after the experiment (post-ASSESS), and some of them held this reduction even 24 h after the stimulation session (post24-ASSESS).…”
Section: Discussionsupporting
confidence: 90%
“…The tremor reduction results observed at the end of IntraStim sessions (short-term effect) are in line with the results reported by others using SurfStim [10]- [12], [28]. All patients who received SATS during IntraStim session (6 out of 6) reduced their tremor during the assessment after the experiment (post-ASSESS), and some of them held this reduction even 24 h after the stimulation session (post24-ASSESS).…”
Section: Discussionsupporting
confidence: 90%
“…Among the review articles, ten studies reported the effects of peripheral electrical stimulation results on patients with ET [18][19][20][21][22][23][24][25][26][27] while ten studies reported on patients with PD [28][29][30][31][32][33][34][35][36][37] and seven studies included both patients with ET and patients with PD [16,17,[38][39][40][41][42]. In order to compare electrical stimulation strategies, some studies also included healthy volunteers that either mimicked tremorgenic activity during experimentation or were subject to artificially induced tremors for experimentation [31,38,41].…”
Section: Target Populationsmentioning
confidence: 99%
“…There are two outliers for the minimum stimulation frequency, Spiegel et al [37], who tested at 2 Hz, 3 Hz, and 5 Hz, and Munhoz et al [18], who tested at 5 Hz, 10 Hz, 50 Hz, and 100 Hz. Certain studies have tested varying the stimulation frequencies while maintaining other stimulation parameters in order to determine optimal tremor reduction values [18,25]. The pulse width is another stimulation parameter and is defined as the duration of each electrical stimulus applied.…”
Section: Stimulation Parametersmentioning
confidence: 99%
See 2 more Smart Citations